2016
DOI: 10.1021/acs.estlett.6b00410
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanotube Arrays Modified Titanium: A Stable, Scalable, and Cost-Effective Bioanode for Microbial Fuel Cells

Abstract: Titanium has been widely used as a dimensionally stable anode in the electrolysis industry because of its excellent corrosion resistance, conductivity, and scalability. However, because of its poor biocompatibility and poor performance as a bioanode, it has drawn little attention in the field of microbial fuel cells (MFCs). This study reports an efficient way to convert a titanium electrode into a high-performance anode for MFCs, in situ growth of titanium dioxide nanotubes (TNs) on its surface. After TN modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 25 publications
0
40
1
3
Order By: Relevance
“…which has been shown to be heavily detrimental to electroactive biofilms [46][47][48]. According to the equations developed previously, the modified Damköhler number (Da mod ) relative to HCO 3 is:…”
Section: Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…which has been shown to be heavily detrimental to electroactive biofilms [46][47][48]. According to the equations developed previously, the modified Damköhler number (Da mod ) relative to HCO 3 is:…”
Section: Surfacementioning
confidence: 99%
“…Mass transfer of the buffering species was no longer able to mitigate the acidification at the bottom of the micro-pillar array. This issue points out, once again, the crucial importance of interfacial acidification [46][47][48] and the importance of ion transport to mitigate it [56].…”
Section: Inefficient Lower Part Because Of Acidificaɵonmentioning
confidence: 99%
“…According to the XRD results, anatase is the dominant phase in both the TNA‐HF and TNA‐NF samples. As calcination was performed at 500 °C, no rutile phase was observed . Figure b,c shows the high‐resolution X‐ray photoelectron spectroscopy (XPS) spectra of the Ti and O regions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements were conducted at a stable ambient temperature (30 ± 2 °C). The anolyte consisted of CH 3 COONa (10 × 10 −3 m ), NH 4 Cl (5 × 10 −3 m ), NaCl (30 × 10 −3 m ), MgSO 4 (8 × 10 −3 m ), and other trace elements . The anolyte was inoculated with the liquid from sludge storage which contains microorganism (in Figure S7, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Surfaces modified with titanium oxide nanowires (Jia et al, 2016) and titanium oxide nanotubes (Feng et al, 2016) have shown that a titanium surface with a nanometre organization constitutes a suitable electrode material for forming microbial anodes, in contrast to smooth titanium, which has proved to be of no interest. After inoculation with effluent from an existing acetate-fed MFC reactor, no biofilm developed on smooth titanium, and consequently no current was produced, while the titanium electrodes coated with nanotubes were completely covered with biofilm and produced 12.7 A m -2 .…”
Section: Take Care When Choosing the Experimental Set-upmentioning
confidence: 99%